“Unfortunately, we couldn’t reach a definitive diagnosis”: the interactional management of uncertainty in genetic counseling (RECIIS, 2024)
This paper examines how participants in genetic counseling sessions interactionally manage situations where the results of tests to investigate the causes of identified fetal malformations are inconclusive or missing. The dataset consists of 54 audio-recorded interactions at a unit specialized in moderate- and high-risk pregnancies at a Brazilian public hospital. Conversation analysis was used to examine the data, revealing that the participants deployed interactional actions that exhibited highly negative valence toward diagnostic inconclusiveness, demonstrating that when there is a motivation for a medical examination, insofar as its results will serve as a basis for subsequent decision-making (in this case about future pregnancies), there is a preference for bad diagnostic news over absent or inconclusive diagnostic news. These findings are consistent with prior interactional studies.